Robotic distal pancreatectomy: Initial experience with the Versius robotic surgical system. Stage 2a IDEAL prospective case series - Francesco Lancellotti; Affan Iqbal; Jenifer Barrie; Panagiotis Stathakis; Thomas Satyadas; Rahul Deshpande; Jegatheeswaran Santhalingam; Nicola de Liguori-Carino; Aali Sheen; Ajith Kumar Siriwardena; Saurabh Jamdar (Clinical Surgical Oncology)
Background: Distal pancreatectomy (DP) is a well-established minimally invasive procedure. However, feasibility and technical details when using Versius robotic surgical system are still unexplored. Method: This is a prospective stage 2a development IDEAL (Idea, Development, Exploration, Assessment and Long-term monitoring) case series. All consecutive robotic DP (RDP), including both splenectomy (DPS) and spleen-preserving DP (SPDP), were analysed. Pre- intra- and post-operative details were prospectively recorded. Results: 6 DPS and 3 SPDP were performed between May 2022 and May 2024. Conversion to open was recorded in one case. The average operating time and robot docking time were 185 ​min (range: 118–300) and 9.3 ​min (range: 3–15), respectively. No reoperation or 90-days mortality were recorded. Ports placement, instruments used, and surgical strategy are described in detail. Conclusion: We present the first series on RDP performed by Versius robotic surgical system. The procedure is safe and feasible, and careful patient selection is required for the first cases.